The role of cannabinoid receptor 2 in bone remodeling during orthodontic tooth movement - Deng-ying Fan; Hao-yan Zhai; Yuan Zhao; Xing Qiao; De-chao Zhu; Hui-Juan Liu; Chunyan Liu (BMC, 2024)
Abstract Background The purpose of this study is to explore the effects of CB2 on bone regulation during orthodontic tooth movement. Methods Thirty male mice were allocated into 2 groups (n = 15 in each group): wild type (WT) group and CB2 knockout (CB2−/−) group. Orthodontic tooth movement (OTM) was induced by applying a nickel-titanium coil spring between the maxillary first molar and the central incisors. There are three subgroups within the WT groups (0, 7 and 14 days) and the CB2−/− groups (0, 7 and 14 days). 0-day groups without force application. Tooth displacement, alveolar bone mass and alveolar bone volume were assessed by micro-CT on 0, 7 and 14 days, and the number of osteoclasts was quantified by tartrate-resistant acid phosphatase (TRAP) staining. Moreover, the expression levels of RANKL and OPG in the compression area were measured histomorphometrically. Results The WT group exhibited the typical pattern of OTM, characterized by narrowed periodontal space and bone resorption on the compression area. In contrast, the accelerated tooth displacement, increased osteoclast number (P < 0.0001) and bone resorption on the compression area in CB2−/− group. Additionally, the expression of RANKL was significantly upregulated, while OPG showed low levels in the compression area of the CB2 − / − group (P < 0.0001). Conclusions CB2 modulated OTM and bone remodeling through regulating osteoclast activity and RANKL/OPG balance.